Quality of Staff Practicing Assessment at Higher Education Schools - Emad Abuallrub; Eissa qadada (University of Science and Technology, Yemen, 2008)
Quality of Staff Practicing Assessment at Higher Education Schools Abstract Faculty members play an important role in enhancing the quality of teaching in higher education, especially with the emerging international standards and benchmarks, as institutional challenges and competitions continue in the new age of globalization and the great affect of communication and information technology. Recently, it is becoming a must for higher education institutes to pay more attention to enhance the quality of faculty members through periodical comprehensive effective evaluation, which will affect positively the quality of the university outcomes. This paper aims to develop a framework for evaluating the performance of faculty members in higher education institutes. The suggested framework is comprehensive, flexible, and objectives. The evaluation process is based on the self-evaluation conducted by the faculty member himself as well as the evaluation of other colleagues in the same department through the peer-to-peer evaluation, the evaluation of the department chair, the evaluation of the dean, and the evaluation of students. Finally, the quality assurance unit at the university records a final grade with recommendations to enhance the performance of the faculty